2018
DOI: 10.1016/j.ijheatmasstransfer.2018.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Boiling performance on surfaces with capillary-length-spaced one- and two-dimensional laser-textured patterns

Abstract: This investigation used laser-processed 25-μm-thick stainless steel foils as heaters in pool boiling experiments under subcooled and saturated conditions at atmospheric pressure. Boling surfaces were modified by a nanosecond fiber laser. In most cases, laser-textured parts on boiling surfaces were spaced apart by a capillary length of water (2.5 mm) and had different shapes and arrangements. Multi-scale micro-cavities (with diameters ranging from 0.2 to 10 μm) on the laser-textured areas of the surfaces provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Similarly, microcavity surfaces were previously shown to considerably enhance the boiling performance, especially the HTC [41,104,105]. Using patterned microcavity surfaces, Voglar et al [106] achieved an HTC of 54.6 kW m −2 K −1 on laser-textured stainless steel. Similarly, Može et al [107] produced microcavities in the size range of approx.…”
Section: Comparison Of Boiling Curves and Heat Transfer Coefficientsmentioning
confidence: 95%
“…Similarly, microcavity surfaces were previously shown to considerably enhance the boiling performance, especially the HTC [41,104,105]. Using patterned microcavity surfaces, Voglar et al [106] achieved an HTC of 54.6 kW m −2 K −1 on laser-textured stainless steel. Similarly, Može et al [107] produced microcavities in the size range of approx.…”
Section: Comparison Of Boiling Curves and Heat Transfer Coefficientsmentioning
confidence: 95%
“…The results indicated the enhancement observed due to rewetting characteristic performed on the modified surface. Voglar et al [7] showed that numerous active nucleation sites caused the significant improvement in peak heat flux. The nucleation sites are developed by creating cavities in microns by laser texturing on surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the -cavities with diverse radii appear due to significant ejection of this remolten material. However, this strategy is not appropriate for processing thin foils (e.g., with a thickness of 25 m) that are required when measuring the transient temperature fields using an IR camera on the backside of the foil, as performed in several experimental studies [34,46,62,84,174], since very high fluences may lead to up to 100 m deep -channels (Fig. 12.13b).…”
Section: Fabrication Of Multiscale -Cavities By Laser Texturingmentioning
confidence: 99%
“…This represents a tremendous capability to study the optimal distribution of active nucleation sites in the context of (i) achieving a uniform temperature field and high heat transfer rates at low superheats; and (ii) delaying the horizontal coalescence of bubbles that 58 prevents a generation of large vapor patches (i.e., to reach high CHF). Some studies [97,174,195] have shown that the optimal distance between the active nucleation sites (regions) that leads to the maximal enhancement of the HTC and CHF roughly corresponds to the capillary length of the working fluid. However, a possible deviations from this theory [84] might be attributed to the fact that the growth time, nucleation frequency and bubble size are not the same for all nucleation sites.…”
Section: Decreased Influence Of Surface Wettability On -Cavity-induced Boiling Performance Enhancementmentioning
confidence: 99%